2021
DOI: 10.1101/2021.03.11.21253352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient maternofetal transplacental transfer of anti- SARS-CoV-2 spike antibodies after antenatal SARS-CoV-2 BNT162b2 mRNA vaccination

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during pregnancy and early infancy can result in severe disease. Evaluating the serologic response after maternal vaccination during pregnancy and subsequent transplacental antibody transfer has important implications for maternal care and vaccination strategies. Objective To assess maternal and neonatal SARS-CoV-2 antibody levels after antenatal mRNA vaccination. Design, Setting, and Participants This study took place at Hadassah Medic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 11 publications
1
38
1
1
Order By: Relevance
“…On the other hand, a recent study conducted in Israel [ 6 ] reported a lower transfer ratio of anti-Spike IgG (median transfer ratio: 0.44) than that observed in our cases. The median time lapse between second dose administration and delivery was 11 days in the Israel cohort, whereas our subjects received the second dose 33 and 42 days before delivery.…”
contrasting
confidence: 97%
“…On the other hand, a recent study conducted in Israel [ 6 ] reported a lower transfer ratio of anti-Spike IgG (median transfer ratio: 0.44) than that observed in our cases. The median time lapse between second dose administration and delivery was 11 days in the Israel cohort, whereas our subjects received the second dose 33 and 42 days before delivery.…”
contrasting
confidence: 97%
“…Three recent studies about mRNA-LNP vaccines in pregnant women, published after this rapid review was finalized, reinforced these findings[74-76]. Shimabukuro el al, published preliminary results from the U.S. surveillance review of the safety of mRNA COVID-19 vaccines during pregnancy[75].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 vaccination in pregnancy induced a robust maternal immune response, with transplacental antibody transfer detectable as early as 16 days after the first dose. Rottenstreich et al, 20 pregnant women who received two doses of SARS-CoV-2 BNT162b2 (Pfizer/BioNTech) mRNA vaccine and found similar antibody response[76]. No safety concern was reported in any of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary finding of mRNA safety of COVID-19 vaccine in pregnant women showed that vaccination is safe in the third trimester of pregnancy ( Shimabukuro et al., 2021 ). In addition to vaccination protecting women against COVID-19 and its complications during pregnancy, emerging evidence has shown transplacental transfer of SARS-CoV-2 antibodies after maternal COVID-19 vaccination during the third trimester, which suggests that maternal vaccination might provide some level of protection to the neonate ( Gill and Jones, 2021 ; Gray et al., 2021 ; Rottenstreich et al., 2021 ). To date, there is still little information on the efficacy and safety of vaccinating pregnant women.…”
Section: Preventionmentioning
confidence: 99%